Brand community identification matters: a dual value-creation routes framework. Issue 3 (18th July 2019) - Chang, Chia-Wen; Ko, Chih-Huei; Huang, Heng-Chiang; Wang, Shih-Ju
Abstract : Purpose: A brand community consists of relationships between a brand and consumers; community members' identiﬁcation with the brand community is a central characteristic of the community. This study aims to provide a comprehensive conceptual framework to investigate how and why such identification-based relationships yield firm- and member-level benefits to participants in the brand community. Design/methodology/approach: This cross-sectional study analyzes data collected through a questionnaire survey of members from the brand community of VW-Golf Club members in Taiwan. The researchers attended the annual meeting of club members and handed out questionnaires directly to the members. The degree centrality of each member was calculated using UCINET 6 for Windows, a social network analysis software application. This study adopts the partial least squares program to evaluate the measurement properties and structural relationships specified in the research model. Findings: The findings suggest that when customers' identification with a brand community becomes salient, they strengthen their emotional attachment to the brand and improve their centrality in the network. Consequently, emotional attachment can serve as a guiding principle in decision-making and thus strengthen brand equity and assessment of brand extensions. Central members will also gain greater benefits, including collaborative opportunities and influence, through their advantageous position in the network. Originality/value: This study makes four main contributions to the brand community literature. First, this is the first empirical study to simultaneously examine the relationships among community identification (customer to community), emotional attachment to the brand (customer to brand) and network centrality (customer to customer). Second, the empirical framework depicts dual value-creation routes that explain how identification-based relationships can yield firm- and member-level benefits. With respect to firm-level benefits, this is the first empirical study to examine the brand equity and assessment of brand extension in the brand community research. Third, this study applies the rarely adopted UCINET 6 software to scrutinize the network data from the brand community. Finally, this paper examines three actions that organizations can leverage to enhance consumer identification with a brand community.